Hydrogen-rich saline attenuates eosinophil activation in a guinea pig model of allergic rhinitis via reducing oxidative stress. Issue 1 (December 2017) - Yu, Shaoqing; Zhao, Chuanliang; Che, Na; Jing, Lin; Ge, Rongming
Abstract Background It is well considered that reactive oxygen species (ROS) plays a prominent causative role in the development of allergic rhinitis (AR), and eosinophils cells as important allergic inflammatory cells contribute to elevating oxidative stress. Hydrogen, emerging as a novel antioxidant, has been proven effective in selectively reducing ROS in animals models of oxidative damage. We herein aim to verify protective effects of hydrogen on eosinophils cells in guinea pigs models of AR. Methods Thirty two guinea pigs were random divided into four groups, and AR model was established through ovalbumin sensitization. The guinea pigs were injected with hydrogen-rich saline (Normal-HRS and AR-HRS group) or normal saline (control and AR group). The frequencies of sneezing and scratching were recorded. The IgE level, blood eosinophil count and eosinophil cationic protein (ECP) level in serum were measured. The serum malondialdehyde (MDA) and superoxide dismutase (SOD) assays were also measured to evaluate oxidative stress. The expression levels of eotaxin mRNA and protein in the nasal mucosa were also determined by real-time RT-PCR, Western blot and immunofluorescence. Results HRS reduced the ROS and MDA levels and increased SOD level in guinea pigs of AR-HRS group accompanied with decreased frequency of sneezing and scratches. Meanwhile, there was a decline of the number of eosinophils cells in blood and of thelevel of ECP in serum in the AR-HRS group. HRS also significantly decreased the expression of eotaxin in nasal mucosa. Conclusion HRS may play a protective role in attenuating allergic inflammation, and suppressing the increase and activation of eosinophils in AR possibly through antioxidation effect of hydrogen.